The Process of Elaborating the Risk Map of a Public School: A Pedagogical Experience (Research, Society and Development, 2019)
The objective of this article is to present the results of a qualitative investigation of a pedagogical project whose objective was to elaborate the Risk Map of a Public School located in the south of Minas Gerais through a pedagogical experience and contextualized between the disciplines Mathematics, Physics, Biology and Chemistry. About 110 students participated in the construction of the risk map. The proposal was to approach with the students the concepts of Risks in the school environment, Accident Prevention, Danger and Safety associated to the concepts of the sciences. The Internal Accident Prevention Commission (CIPA) at the school was implemented, and the school's Risk Map was prepared by the students along with the guidance of the science teachers. The elaboration of the Risk Map served as an instrument of teaching and learning according to the results of the work, which enabled the development of a culture of safety and accident prevention, besides solidifying knowledge in science.